Apresentação da seção "O Rural, a ciência e o meio ambiente: um debate necessário" - Both, Marcio; Pombo, Nívia; Garcia, José Luís (Anos 90, 2024)
Apresentação da seção "O Rural, a ciência e o meio ambiente: um debate necessário"